Generative Artificial Intelligence as a Cultural Mediator in Higher Education Learning: A Scoping Review - Rachmat Satria (IQRO: Journal of Islamic Education, 2026)
The rapid expansion of generative artificial intelligence (Gen AI) in higher education is reshaping not only learning practices but also the cultural conditions through which students engage with knowledge, academic communities, and their responsibilities as learners. While existing research has predominantly examined Gen AI through technological, pedagogical, and ethical perspectives, its role in transforming learning culture remains insufficiently synthesised. This study aims to synthesise how Gen AI reshapes learning culture in higher education by examining transformations in learning practices, academic norms, academic identity, learning interactions, and self-regulated learning. Guided by the JBI methodology and reported in accordance with PRISMA-ScR, this scoping review identified, appraised, and thematically synthesised 25 peer-reviewed studies published between 2020 and 2026. The synthesis indicates that AI-mediated learning culture emerges through dynamic interactions among Gen AI affordances, academic norms, learner identity, learning interactions, and self-regulation mechanisms. Gen AI therefore operates not merely as a learning tool, but as a socio-cultural mediator that influences how students study, produce knowledge, collaborate, and negotiate academic responsibility. Drawing on these findings, the review proposes an AI-Mediated Learning Culture Framework that maps the interrelationships between technological affordances, academic practices, and learner agency. This conceptual synthesis offers directions for empirical research and supports higher education institutions in designing AI-responsive learning environments.